2015
DOI: 10.5562/cca2647
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons Between Tridentate Bis(benzazoles)-pyridine and Bis(benzazoles)triazine Ligands: a Theoretical Study

Abstract: Twelve bis(benzazole) structures with potential ligand character were investigated by means of computational chemistry. Global and local reactivity descriptors within DFT (Density Functional Theory) theory (Fukui functions, chemical potential, hardness, electrophilicity index) have been computed at B3LYP/6-31G(d,p) level of theory. NICS(0) (Nucleus Independent Chemical Shift) index computations were employed for the evaluation of the local aromatic character of each heterocyclic moiety. Best results have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studies have shown that they are rapidly converted to toxic metabolites [2], which bind proteins in high proportions and thus persist for long periods (weeks or even months) in food products. Those metabolites are 1aminoimidazolidine-2,4-dione (AHD), 3-amino-5morpholinomethyl-2-oxazolidinone (AMOZ), 3-amino-2oxazolidone (AOZ) and semicarbazide (SEM) [3][4][5].…”
mentioning
confidence: 99%
“…Studies have shown that they are rapidly converted to toxic metabolites [2], which bind proteins in high proportions and thus persist for long periods (weeks or even months) in food products. Those metabolites are 1aminoimidazolidine-2,4-dione (AHD), 3-amino-5morpholinomethyl-2-oxazolidinone (AMOZ), 3-amino-2oxazolidone (AOZ) and semicarbazide (SEM) [3][4][5].…”
mentioning
confidence: 99%